Réponses

Meilleure réponse !
2014-04-09T12:53:41+02:00
A= 3 - (2t - 5) - (1 +(7 - 3t))
  = 3 - 2t + 5 - 1 - (7 - 3t)
  = 3 - 2t + 5 - 1 - 7 + 3t
  = 3t - 2t + 3 + 5 - 1 - 7
  = t 

E= 12 - 3(2x - 5) - 2(3x + 4)(6 - 5x)
  = 12 - 6x + 15 - 2 ( 18x - 15x² - 20x + 24)
  = 12 - 6x + 15 - 36x + 15x² + 40x - 48
  = 15x² - 6x - 36x + 40x + 12 - 48
  = 15x² - 2x - 36
Je te fais le E aussi ?
Oui stp
j'ai édité le post. Vérifie tout de même au cas où. Sur PC c'est moins clair que sur une feuille xD
d'accord merci
de rien